Polar Ampliﬁcation Projected by Energy Balance Model with Nonlinear Parametrization of Outgoing Longwave Radiation - Kovalevsky, Dmitry V.; Alekseev, Genrikh V. (Discontinuity, Nonlinearity, and Complexity, 2026)
A linear energy balance model (EBM) of polar amplification (PA) developed by Langen and Alexeev (2007) is modified by replacing the conventional linear parametrization of outgoing longwave radiation (OLR) with a more accurate nonlinear (quadratic) approximation for OLR. The nonlinear version of the model is studied analytically and numerically. The numerical results presented in the paper convincingly demonstrate the importance of adopting the nonlinear approximation for parametrizing the OLR in EBMs. The simulation results yielded by the nonlinear version of the model are visibly different from those provided by the linear model, especially for simulations of climate change in high latitudes and for quantification of PA with dedicated indices.